A balance between excitatory and inhibitory synapses is controlled by PSD-95 and neuroligin - Prange, Oliver (National Academy of Sciences, 2004)
Factors that control differentiation of presynaptic and postsynaptic elements into excitatory or inhibitory synapses are poorly defined. Here we show that the postsynaptic density (PSD) proteins PSD-95 and neuroligin-1 (NLG) are critical for dictating the ratio of excitatory-to-inhibitory synaptic contacts. Exogenous NLG increased both excitatory and inhibitory presynaptic contacts and the frequency of miniature excitatory and inhibitory synaptic currents. In contrast, PSD-95 overexpression enhanced excitatory synapse size and miniature frequency, but reduced the number of inhibitory synaptic contacts. Introduction of PSD-95 with NLG augmented synaptic clustering of NLG and abolished NLG effects on inhibitory synapses. Interfering with endogenous PSD-95 expression alone was sufficient to reduce the ratio of excitatory-to-inhibitory synapses. These findings elucidate a mechanism by which the amounts of specific elements critical for synapse formation control the ratio of excitatory-to-inhibitory synaptic input.